DEVELOPMENT OF AN ORDERING LOT-SIZE MODEL OF BOTTLE OF ADDICTEA PACKAGING UNDER LIFETIME EXPIRATION PERIOD - Sri Rahayu, Lisna
The Addictea is a food and beverage company produced bottled drinking with milktea based ingredient. The Addictea demand which is constantly increasing requires a good preparation on amount as well as time of the product ingredients and other raw materials. Bottles is one of required supplies of product packaging. The bottle has a short life in 14 days. Inaccuracies in calculating order lot size for bottle can result in an overflow of supplies and then number of expired life bottled are increasing. Currently, ordering lot size for bottle is 10.000 units/two-weeks for both size 240 ml and 450 ml. The order size leads to a high total inventory costs due large number of bottle’s inventory and expired life of bottle. Therefore, this research conducts to development a model for determining ordering lot size by considering the bottle lifetime expiration period. We developed the model based on the basic on the basic model Q. The proposed model covered critical characteristics such as normally distributed demand and product lifetime expiration period. The performance criteria of the model are to minimize total inventory costs that consists of purchasing, ordering, holding, shortage, and product expired cost. The decision variable of the model is to find the number of optimal order lot size as well as the reorder point. To solve the proposed model, we proposed a heuristic approach. The experiment results showed that, the optimal order lot for 240 ml bottle is 4.550 units and reorder point is 4.848 units, with total inventory costs are Rp326.326/day. While the optimal order lot size for 450 ml bottle is 3.696 units and reorder point is 4.069 units, with total inventory costs are Rp514.710/day. This results in inventory cost saving for both types of bottle are 89% for 240 ml and 88% for 450 ml size. Based on the results, we can conclude that the optimal order lot size is equal to the number of inventories during expiration period.